2022
DOI: 10.1182/bloodadvances.2021004537
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, pathophysiology, and therapy of poor graft function post–allogeneic stem cell transplantation

Abstract: Poor graft function (PGF) defined by the presence of multi-lineage cytopenias in the presence of 100% donor chimerism, is a serious complication of allogeneic stem cell transplant (alloSCT). Inducers or potentiators of allo-immunity such as CMV reactivation and graft versus host disease (GVHD) are associated with the development of PGF, however more clinical studies are required to establish further risk factors and describe outcomes of PGF. The pathophysiology of PGF can be conceptualized as dysfunction relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 99 publications
1
35
0
Order By: Relevance
“…Widely proposed is the “seed, soil and climate” model for the pathophysiology of PGF ( 6 , 29 ). Current literature suggests hematopoietic stem cells (seed) abnormalities have a causative role in PGF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Widely proposed is the “seed, soil and climate” model for the pathophysiology of PGF ( 6 , 29 ). Current literature suggests hematopoietic stem cells (seed) abnormalities have a causative role in PGF.…”
Section: Discussionmentioning
confidence: 99%
“…However, hematologists have noticed that even if the patients achieved initial hematopoietic reconstitution and maintain complete donor-originated hematopoietic cells, they may develop intractable multilineage cytopenia afterwards ( 4 , 5 ). This is defined as secondary poor graft function (sPGF), and it occurs in 5-27% of post-transplantation cases ( 6 ). Patients with sPGF lose their initial hematopoietic reconstitution, which leads to increased risks of severe infection, major bleeding events, and other life-threatening complications after transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2b, c. These cases demonstrate PGF which has been reviewed in detail previously [34] and will be used to frame a discussion regarding pathophysiology and potential treatments.…”
Section: Poor Graft Function (Pgf)mentioning
confidence: 92%
“…A study conducted by the Severe Aplastic Anemia Working Party of the European Society for Blood and Marrow Transplantation (SAAWP-EBMT) showed that graft-versus-host disease-free, relapse-free survival (GRFS) of allo-HSCT for AA was only 69% over 5 years [ 9 ]. However, the remaining patients still have complications, such as graft-versus-host disease (GVHD) [ 10 ], virus infection [ 11 ], poor graft function [ 12 ], and so on. Although the treatment of AA in Western medicine is developing rapidly, there are still many nonnegligible clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%